`Second Best' Congestion Taxes in Transportation Systems - Bertrand, Trent J. (Econometrica, 1977)
[The optimal policy prescription in response to congestion on a traffic network involves taxes levied so as to increase the private costs of vehicle use by the amount of the costs imposed on other users of the system. However, technical and political constraints may make this taxation policy infeasible. Using assumptions on the effect of taxation on the level and structure of demandfor transportation services, this paper provides guidelines for taxation (and possibly subsidization) in a multi-mode traffic system in which such constraints are effective.]